Share Happiness. - Nurdrat (karachi, Nudrat book house, 2023)
In this book Alina is well mannered who is sharing things with Saliha.
This book is dedicated to promote good manner like sharing in children.
children of age 5-8 years.
Keywords: fiction story -- Pakistan -- Pakistan